Aerial visibilities: Towards a visual sociology of the sky - Bratchford, G.; Zuev, D. (Visual Studies, 2020)
For many people, watching the sky, even if only momentarily, is an act of escapism, absorption and fantasy flow. We gaze at the stars or track a passing satellite; some of us even travel, recreationally or as hobbyists, to look at the dark skies in what is becoming known as astrotourism. Whether it is tourists watching the atmospheric phenomenon of the aurora borealis beyond the Arctic Circle – a flickering and unpredictable light show in the night sky – or tourists on the rooftops in Las Vegas watching mushroom clouds and orange glow at the Nevada test site (in the 1950s the Las Vegas chamber of commerce issued special tourist calendars with dates, times and the best ‘spots’ to observe detonations). The culture of skyward observations has long had an effect on individuals, communities and spaces.